PEMBINAAN APARATUR PEMERINTAH DALAM RANGKA MENINGKATKAN KUALITAS KERJA (Suatu Studi di Kecamatan Siau Timur) - MOHEDE, HEZKY (JURNAL POLITICO, 2013)
ABSTRACTOrganization represent medium activity of people in tired effort target. To execute and reach target, hence needed by human resource. Human resource top-drawer element or asset among other organizational elements. Important human resource because of influencing organizational effectiveness and efesiensi, and human resource represent expenditure of organizational fundamental in running its duty. Human resource in relation to this matter is Public Servant Of Civil that is as activator of administration mechanism wheel in governance organization. Accurate writer and study about